Identification And Detection Of Proteolytic Activity Of Endophite Bacterial Isolated From Avicennia Marina Leaves In Mempawah Mangrove Center - Fani, Evi Fania; Rahmawati, Rahmawati; Kurniatuhadi, Rikhsan (LenteraBio : Berkala Ilmiah Biologi, 2022)
Abstract. Endophytic bacteria are bacteria that live in healthy plant tissue without damaging the plant tissue itself. This study aims to determine the morphological and physiological characteristics, as well as to determine the proteolytic activity of the genus of endophytic bacteria found in Avicennia marina leaves. The research was conducted through the stages of bacterial isolation, morphological characterization, physiological test which includes biochemical factor test and proteolytic activity test, as well as identification. The method used is a systematic sampling method and the data collected were analyzed descriptively. The characteristics of endophytic bacteria obtained have morphological characteristic with rounded colony shapes, flat and wavy edgs, convex elevation, white to yellow colony color, gram positive and negative with cocci and bacillary cell shapes. Physiological tests on the salinity, pH and temperature tests of all isolates produced a positive reaction. The results obtained 6 isolates of endophytic bacteria from Avicennia marina leaves which have similarities with members of the genus Staphylococcus, Bacillus, Pseudomonas and Micrococcus. The isolates obtained did not have proteolytic activity.